Should patients with pollen fruit syndrome be prescribed an automatic epinephrine injector?. Issue 4 (August 2016) - Katelaris, Constance H.
Abstract : Purpose of review: The review outlines recent insights into our understanding of the complex relationships between pollen and plant food sensitization patterns resulting in the pollen fruit syndrome and the possible risk, upon ingestion, of generalized symptoms rather than localized oropharyngeal reactions. Appreciation of this risk will inform management strategies, which include epinephrine prescription. Recent findings: In recent times, the ability to examine molecular components of foods and pollen has allowed further delineation of reactivity patterns. These reveal complex patterns of IgE reactivity and sensitization pathways. More precise definition of these patterns will allow a more accurate analysis of risk of severe food reactions following ingestion. Summary: Despite improvement in diagnostic tests, there remains no completely reliable way to determine whether an individual with pollen fruit syndrome is at risk of a systemic reaction. The decision to prescribe an epinephrine autoinjector must be based on a risk assessment for the individual patient.